2011
DOI: 10.1038/ismej.2011.69
|View full text |Cite
|
Sign up to set email alerts
|

Identification and isolation of active N2O reducers in rice paddy soil

Abstract: Dissolved N 2 O is occasionally detected in surface and ground water in rice paddy fields, whereas little or no N 2 O is emitted to the atmosphere above these fields. This indicates the occurrence of N 2 O reduction in rice paddy fields; however, identity of the N 2 O reducers is largely unknown. In this study, we employed both culture-dependent and culture-independent approaches to identify N 2 O reducers in rice paddy soil. In a soil microcosm, N 2 O and succinate were added as the electron acceptor and dono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(56 citation statements)
references
References 52 publications
2
54
0
Order By: Relevance
“…Previous studies utilized conventional primer sets to analyze nirK and nirS of denitrifiers that belonged primarily to alpha-, beta-, and gamma-proteobacteria from various environmental samples (Braker et al, 2000;Heylen et al, 2006;Smith et al, 2007;Ishii et al, 2011;Palmer et al, 2012). However, our phylogenetic analysis of the available nirK and nirS showed that a greater diversity of microorganisms possess nirK or nirS, including Actinobacteria, Bacteroidetes, Chloroflexi, Nitrospirae, Spirochetes, Planctomycetes, NC10, and even the archaeal phylum Euryarchaeota (Figure 1).…”
Section: Discussionmentioning
confidence: 74%
“…Previous studies utilized conventional primer sets to analyze nirK and nirS of denitrifiers that belonged primarily to alpha-, beta-, and gamma-proteobacteria from various environmental samples (Braker et al, 2000;Heylen et al, 2006;Smith et al, 2007;Ishii et al, 2011;Palmer et al, 2012). However, our phylogenetic analysis of the available nirK and nirS showed that a greater diversity of microorganisms possess nirK or nirS, including Actinobacteria, Bacteroidetes, Chloroflexi, Nitrospirae, Spirochetes, Planctomycetes, NC10, and even the archaeal phylum Euryarchaeota (Figure 1).…”
Section: Discussionmentioning
confidence: 74%
“…In addition, the amended NoFer soil at low moisture level had an abundant Burkholderiales at days 20 and 200, as well as Actinomycetales at day 80 of the incubation period. Most Burkholderiales are identified as the reducers of soil dissolved N 2 O (Ishii et al, 2011), so in the presence of stubble these bacteria maybe have strong N 2 O-reducing ability in soils with low fertility and moisture levels. Sometimes the growth of Actinomycetales can be well maintained at low fertility and moisture levels, because Actinomycetales can explore soil space with the mycelium for nutrient acquisition at the soil-straw interface (Frey et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In order to elucidate the microbes responsible for N2O reduction in rice paddy soils, Ishii et al (44) employed both culture-independent (SIP analysis) and culture-dependent (FSC isolation) methods. Similar to the results obtained in rice paddy soils under denitrification conditions, Herbaspirillum sp.…”
Section: N2o Production and Reductionmentioning
confidence: 99%